Implementation of Music Education at Indonesian School of Bangkok - Thubany Amas (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
The implementation of music education at the Indonesian School of Bangkok (Sekolah Indonesia Bangkok/ SIB) plays a significant role in fostering students' cognitive and artistic development, while also contributing to the preservation and promotion of Indonesian culture abroad. This qualitative study, employing an autoethnographic approach, aims to describe the music education practices at SIB, focusing on the materials taught, the teaching methods used, and the impact of these practices on cultural diplomacy. Through various traditional Indonesian musical instruments such as angklung, kolintang, cethik, and gamelan, students are not only taught technical music skills but also the cultural values embedded in each instrument and its repertoire. Methods such as demonstration, drill, Kodály, experiential learning, and discussion are applied to ensure students develop a comprehensive understanding of music. Additionally, through cultural performances, students can introduce Indonesian music to the Thai public and international audiences, enhancing Indonesia’s cultural diplomacy. The study highlights how music education at SIB serves as both an educational tool and a medium for cultural exchange, promoting Indonesian arts and strengthening cultural ties between Indonesia and the global community.